The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.21608/jaauth.2021.68852.1160
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Impact of Organizational Support, Service Training and Empowerment on Employees' Affective Commitment and Service Recovery Performance: Hotel Front Office Department’s Perspective

Abstract: This study investigated the interrelationship of some management practices of service quality, as manifested by front office employees' appraisal of organizational support, service training and empowerment and service recovery performance through their affective commitment in the Egyptian hotel sector. This research reports the findings of questionnaire survey distributed to 219 employees from the front office department of five-star hotels in Cairo. Previously developed and validated measures for organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…They contribute to the achievement of their organization's goals, comply with regulations, adapt to undesired circumstances without complaining, and avoid making problems with their colleagues. This finding aligns with prior studies which highlighted the contribution of PE in motivating positive behaviors and decreasing WI (Elziny and Mohamed, 2021;Maan et al, 2020;Ojo and Tamunoipiriala, 2019;Liu et al, 2018;Chiang and Hsieh, 2012;Naderi and Hoveida, 2013;Spreitzer, 2008;Malik et al, 2013;Aksel et al, 2013;Gorji, and Ranjbar, 2013).…”
Section: Relationship Between Pe and Wisupporting
confidence: 92%
“…They contribute to the achievement of their organization's goals, comply with regulations, adapt to undesired circumstances without complaining, and avoid making problems with their colleagues. This finding aligns with prior studies which highlighted the contribution of PE in motivating positive behaviors and decreasing WI (Elziny and Mohamed, 2021;Maan et al, 2020;Ojo and Tamunoipiriala, 2019;Liu et al, 2018;Chiang and Hsieh, 2012;Naderi and Hoveida, 2013;Spreitzer, 2008;Malik et al, 2013;Aksel et al, 2013;Gorji, and Ranjbar, 2013).…”
Section: Relationship Between Pe and Wisupporting
confidence: 92%
“…The Likert scale evaluates respondents' answers based on five different evaluation criteria (1 is strongly disagree until 5 is strongly agree). Measurement of servant leadership (SL) variables employed assessment indicators proposed by Qiu and Dooley (2019), nonphysical work environment (NEW) variables utilized assessment indicators from Abdou et al (2022), and affective commitment (AC) variables were measured using indicators from Elziny and Emam (2021). Employee performance (EP) variables were gauged based on indicators outlined by Koopmans et al (2012).…”
Section: Collecting Data Methodsmentioning
confidence: 99%
“…The existence of an understanding between the values, vision, mission, goals, and norms adopted by an organization and the employee's personality allows affective commitment to grow (Shao et al, 2022). Indicators of affective commitment are identification, involvement, and attachment (Elziny & Emam, 2021).…”
Section: Affective Commitmentmentioning
confidence: 99%
“…Moreover, another study was performed in nearly 300 city and country clubs, which demonstrated that increased employee empowerment was directly related to the performance of the employees, especially the customer service employees ( Elziny, 2021 ). The research showed that the participation of employees greatly increased after the policy of employee empowerment was implemented in these city and country clubs, leading to higher employee commitment by employees and higher operational capacity.…”
Section: Literature Reviewmentioning
confidence: 99%